On Slow Money - Weld, Linzee (Maine Policy Review, 2011)
This short article discusses “Slow Money,” a call to people to invest in local farms and food-related businesses. Slow Money Maine (SMM).is a network providing a means for individuals to connect to grow and strengthen individual businesses and provide support for start-ups.
Keywords: Maine; slow money